Implementasi Metode Kriptografi Advanced Encryption Standard 256 Bit Berbasis Web dan Mobile Pada Pengamanan Dokumen Notaris - Aditya, Febrian; Romli, Moh. Ali (TIN: Terapan Informatika Nusantara, 2025)
Document security is an essential aspect of notarial practice since notarial documents hold high legal value and must be kept confidential. The digitization of documents improves efficiency but also introduces new risks to data protection. This study aims to develop a web- and mobile-based notarial document security application implementing the Advanced Encryption Standard (AES-256) encryption method to maintain the confidentiality and integrity of digital documents. The research adopts a qualitative approach with a case study conducted at the office of Notary Wavie Laksono Putro, S.H., M.Kn. Data were collected through interviews, observations, and documentation studies of existing document management processes. Data analysis was performed descriptively to assess system requirements, encryption effectiveness, and user responses to the application. The testing results show that the system can successfully encrypt and decrypt documents with a 100% success rate across all testing scenarios. The system also proved more efficient in document management compared to manual processes at Notary Wavie Laksono Putro’s office. This research contributes to the development of cryptography-based digital security systems applicable to improving data protection in modern notarial practices.